How do the variations in military organization influence the implementation of economic coup proofing mechanisms in the MENA Region? The cases of Jordan, Syria and Egypt - Abou Refaie, Reem Mahmoud (AUC Knowledge Fountain, 2015)
The Arab uprisings have certainly caused quiet the watershed among scholars of civil-military relations. Incumbents that were rendered coup proofed were suddenly falling victim to the mercy of their militaries. Questions like, “Why is coup proofing more successful in some cases more than others?” and “Does coup proofing work?” guided the literature on coup proofing in the last decade even more so in the last four years. Significant research has been undertaken outlining possible reasons for the success/failure of coup proofing. Some authors have even questioned the viability of the coup-proofing process, but yet, no clear reasoning for variations in outcomes of coup-proofing appear to have emerged from the literature to date. Thus, this thesis attempts to take a step back and examine the process through which coup proofing mechanisms are formulated. More particularly, I pose the following questions: Why are there variations in the implementation of some coup proofing mechanisms and what are the conditions contributing to this variation in application? Escaping thus the trap of studying coup proofing as a monolithic process, this thesis studies the variation in the application of economic coup proofing – approach, technique and implementation – in relation to the organizational features of the military on which the tactics are implemented. To achieve this, the study conducts a qualitative comparison between Jordan, Syria and Egypt. All the regimes in question applied economic coup proofing as a means of buying military loyalty and they also bought them out of day-to-day politics. The Syrian Military, for example, relies on personalized and illicit activity – smuggling and currency dealing – as a means of generating military incentives. This is in comparison to the Egyptian and Jordanian Militaries who profit from controlling large industrial complexes. Questions explaining the reasons behind such variation remain unanswered. While it is theoretically valuable to study economic coup proofing as simply a means of buying off officers that ties the military to the incumbent, it is intuitively compelling to study it as a form of military business. This in-turn affects the military’s autonomy vis-à-vis the incumbent but also influences the military’s relation with society at large